Endotoxemia and endotoxin shock disease, diagnosis and therapy - Ronco, Claudio 1951-; Piccinni, Pasquale; Rosner, Mitchell H. (Karger, 2010)
The presence of endotoxin in the bloodstream is the consequence of an immunological response triggered by bacterial invasion of the host. This condition leads to altered cardiovascular function, lung dysfunction and acute kidney injury. Removing as much as possible of the circulating endotoxin is therefore imperative to mitigate its biological and clinical effects at the cellular, tissue and organ levels. The publication at hand summarizes the basic mechanisms, rationale and clinical results of a new therapeutic approach that promises to attain this goal: It consists of a specific hemoperfusion process that utilizes cartridges with immobilized polymixin B in an extracorporeal circuit.Containing contributions by renowned researchers, this book represents as a milestone in the field of extracorporeal therapies in sepsis. It will be a valuable reference work for both basic scientists and clinical professionals who want to keep abreast of current developments
Extracorporeal therapies and the management of sepsis
Keywords: Endotoxikose; Hämoperfusion; Polymyxin B; Endotoxinschock; Aufsatzsammlung